Vitamin D deficiency among subfertile women: case-control study. (2nd April 2016) - Al-Jaroudi, Dania; Al-Banyan, Nora; Aljohani, Naji J.; Kaddour, Ouhoud; Al-Tannir, Mohamad
Abstract: Objective : The objective of the study is to compare the dietary vitamin D and calcium intake among subfertile women (cases) versus pregnant women (controls) and to determine the vitamin D levels in the subfertile and pregnant women. The study design was an observational case-control study where a total of 181 (83 previously diagnosed subfertile cases from various causes and 98 pregnant controls) women of reproductive age. A validated questionnaire was used where it focused on key indicators evaluating vitamin D-related factors. Blood was withdrawn for the measurement of serum calcium, albumin and phosphate to exclude secondary causes that might affect vitamin D level. Results : The prevalence of vitamin D deficiency was significantly higher in the subfertile group than controls (59.0% versus 40.4%; p  < 0.01). Calcium supplements intake was significantly higher in controls than the subfertile group (64.6% versus 10.0%; p value < 0.001). Total dietary vitamin D intake (> 400 IU/day) was significantly higher in the controls than the subfertile group. Conclusion : Vitamin D deficiency is prevalent among subfertile women. Optimization of serum calcium and vitamin D levels is encouraged.